Analisis Variasi Penggunaan Increment Terhadap Informasi Citra Ct Scan Kepala Pada Kasus Stroke Non Hemoragic (SNH) Di Instalasi Radiologi Rsud Bali Mandara - Natalia Liliosa Miu; Ni Putu R. Jeniyanthy; I Made Purwa Darmita (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background:Non-hemorrhagic strokeis a cerebrovascular disease that occurs when the blood supply to part of the brain is suddenly interrupted by occlusion, usually caused by thrombosis, embolism, and focal hypoperfusion which can cause a reduction or disruption in cerebral blood flow (CBF) and affect neurological function due to lack of glucose and oxygen. Computed tomography scanning (CT Scan) of the head is a special examination of the head that uses tomography techniques with X-ray beams penetrating the patient's head from various directions using a computer system to produce anatomical images in axial, sagittal and coronal planes..One of the parameters for a CT scan of the head is Increment Reconstruction. Reconstruction Increment is the distance between reconstruction images in volume data. Method: Typeresearch is quantitative with an experimental approach, carried out in July-August 2023 at Bali Mandara Regional Hospital. The population and sample of this study were 10 patients with indications of non-hemorrhagic stroke. Results :research results from the overall Friedman test on CT scans of the head with clinical non-hemorrhagic stroke using variations in reconstruction increments of 0.5mm, 0.9mm, 1.5mm, 2mm, the results of the most optimal anatomical image information in producing images from 4 variations of increments, namely in the 2mm increment reconstruction which has the highest mean rank value, namely 3.30 in the thalamus area, 3.40 in the lateral ventricle area, 3.25 in the white matter area, 3.40 in the gray matter area, 3.40 in the lesion area hypodense/infarction of 3.25. Conclusion:From the results of the Friedman test on CT scans of the head with clinical non-hemorrhagic strokes using variations in reconstruction increments of 0.5mm, 0.9mm, 1.5mm, 2mm against anatomical criteria, the most optimal value in producing an image is at a reconstruction increment of 2mm which has the highest mean rank value.